Glutamate and GABA in Vestibulo-Sympathetic Pathway Neurons - Holstein, Gay R.; Friedrich, Victor L. Jr.; Martinelli, Giorgio P. (Frontiers in Neuroanatomy, 2016)
The vestibulo-sympathetic reflex actively modulates blood pressure during changes in posture. This reflex allows humans to stand up and quadrupeds to rear or climb without a precipitous decline in cerebral perfusion. The vestibulo-sympathetic reflex pathway conveys signals from the vestibular end organs to the caudal vestibular nuclei. These cells, in turn, project to pre-sympathetic neurons in the rostral and caudal ventrolateral medulla (RVLM and CVLM, respectively). The present study assessed glutamate- and GABA-related immunofluorescence associated with central vestibular neurons of the vestibulo-sympathetic reflex pathway in rats. Retrograde FluoroGold tract tracing was used to label vestibular neurons with projections to RVLM or CVLM, and sinusoidal galvanic vestibular stimulation was employed to activate these pathways. Central vestibular neurons of the vestibulo-sympathetic reflex were identified by co-localization of FluoroGold and cFos protein, which accumulates in some vestibular neurons following galvanic stimulation. Triple-label immunofluorescence was used to co-localize glutamate- or GABA- labeling in the identified vestibulo-sympathetic reflex pathway neurons. Most activated projection neurons displayed intense glutamate immunofluorescence, suggestive of glutamatergic neurotransmission. To support this, anterograde tracer was injected into the caudal vestibular nuclei. Vestibular axons and terminals in RVLM and CVLM co-localized the anterograde tracer and vesicular glutamate transporter-2 signals. Other retrogradely-labeled cFos-positive neurons displayed intense GABA immunofluorescence. Vestibulo-sympathetic reflex pathway neurons of both phenotypes were present in the caudal medial and spinal vestibular nuclei, and projected to both RVLM and CVLM. As a group, however, triple-labeled vestibular cells with intense glutamate immunofluorescence were located more rostrally in the vestibular nuclei than the GABAergic neurons. Only the GABAergic vestibulo-sympathetic reflex pathway neurons showed a target preference, projecting predominantly to CVLM. These data provide the first demonstration of two disparate chemoanatomic vestibulo-sympathetic reflex pathways.